Validation of the questionnaire to measure Chilean teachers’ perception of school violence and coexistence management (VI+GEC) - Muñoz-Troncoso, Flavio; Halberstadt, Amy; Cuadrado-Gordillo, Isabel; Riquelme-Mella, Enrique; Miranda-Zapata, Edgardo; Legaz-Vadímisrkaya, Ekaterina; Sepúlveda-Bernales, Valeria; Salamanca-Aroca, Claudia; Muñoz-Troncoso, Gerardo (Frontiers in Psychology, 2024)
In this article, we present the development and validation of a psychometric scale that measures the teacher’s perception in the Chilean school system with respect to elements of school violence and coexistence management. The novelty lies in the incorporation of factors that address violence from teachers to students, from students to teachers and coexistence management. A total of 1072 teachers from the Northern, Central, Southern and Metropolitan macro-zones of Chile participated, with ages between 22 and 76 years (M=44.56; SD=10.52) and from 1 to 54 years of work (M=17.14; SD=10.38). 76.3% identify with the female gender and 23.7% with the male gender. Of the teachers, 78.4% worked mainly in the classroom and the rest performed managerial or administrative functions outside the classroom in the school. The school violence and coexistence management questionnaire for teachers (VI+GEC) was used. The validity of the scale was demonstrated by means of Confirmatory Factor Analysis, convergent validity analysis and discriminant validity. Reliability was demonstrated by means of McDonald’s omega coefficient in all the factors of the scale. An analysis with Structural Equation Modeling (SEM) found a mean, and statistically significant influence of the perception of coexistence management on the perception of school violence. The findings are discussed in terms of previous research on school violence and coexistence management.